Transcriptional Regulation of Channelopathies in Genetic and Acquired Epilepsies - van Loo, Karen M. J.; Becker, Albert J. (Frontiers in Cellular Neuroscience, 2020)
Epilepsy is a common neurological disorder characterized by recurrent uncontrolled seizures and has an idiopathic “genetic” etiology or a symptomatic “acquired” component. Genetic studies have revealed that many epilepsy susceptibility genes encode ion channels, including voltage-gated sodium, potassium and calcium channels. The high prevalence of ion channels in epilepsy pathogenesis led to the causative concept of “ion channelopathies”, which can be elicited by specific mutations in the coding or promoter regions of genes in genetic epilepsies. Intriguingly, expression changes of the same ion channel genes by augmentation of specific transcription factors early after an insult can underlie acquired epilepsies. In this study, we review how the transcriptional regulation of ion channels in both genetic and acquired epilepsies can be controlled, and compare these epilepsy “ion channelopathies” with other neurodevelopmental disorders.